Performance Audit and Public Sector Budgetary Efficiency in Southwest Nigeria - OLAOYE, Festus Oladipupo; ADEDEJI, Ayodeji Quadri (Journal of Accounting, Business and Finance Research, 2019)
This study examined performance audit and public sector budgetary efficiency in southwest Nigeria. Specifically, the study examined the effect of total quality management (TQM) on budgetary efficiency in Southwest Nigeria, Public service value (PSV) on budgetary efficiency in Southwest Nigeria and Government accountability system (GAS) on budgetary efficiency in Southwest Nigeria. Primary method of data collection was employed, through structured questionnaire and it was sourced from the Ministry of Finance, Ministry Rural Development, Ministry Health, Ministry Work and Infrastructure in selected Southwest States in Nigeria, which are, Lagos, Oyo and Ogun. Data were analyzed using both descriptive and inferential statistics. Descriptive analyses conducted in the study include frequency table, and pie chart while inferential analyses conducted in the study include linear regression and ANOVA analysis. F.test used to test the overall significance of the regression model while the coefficient of determinant r2, was used to determine how much variation the dependent variable was explained by the independent variable. Result revealed that coefficient of determination (r2) of total quality management, public sector value and government accountability system were 0.730, 0.654 and 0.433 which implies that about 73%, 65.4% and 43.3% variation in budgetary efficiency of the selected states can be explained by total quality management, public sector value, government accountability system in individual States. The study found out that total quality management (TQM), public service value (PSV) and government accountability system (GAS) indicated positive and significant effect on budgetary efficiency in southwest Nigeria, (.854, p .000 < 0.05), (809, p 0.003 < 0.05) and (.658, p .002 < 0.05) respectively. The overall regression model of (Total quality management, Public sector value and Government accountability system in the selected States) are significant in terms as F calculated (256.641, 83.084 and 61.846) are greater than F critical (3.89) respectively. The study concluded that total quality management, public service value and government accountability system have significant effects on public sector budgetary efficiency in Southwest Nigeria, and positively related.